Evaluation of E-Commerce Systems: Comparative Study Before and During the COVID-19 Pandemic - Júnior, Demétrio Mendonça; Dallagnol, Mathäus Freitag; Martins, Vanessa Quadros; Freitag, Viviane Costa (Journal of Information Systems and Technology Management, 2023)
The use of e-commerce stimulated by social isolation due to COVID-19, requires accompanying measures, among them, the evaluation of the success of the Information System (IS). Researchers has been dedicated for over 30 years to evolving and adapting IS evaluation models. This investigation empirically tests the theoretical model of DeLone & McLean (2004) in two distinct periods, before and during the pandemic. A survey was conducted with 329 B2C e-commerce consumers. Using structural equation modeling to analyze the data. Results showed that, before the pandemic, e-commerce users did not perceive value in the quality of the system's information and, during the pandemic, the perception changed. Furthermore, they also started to recognize more value in the quality of the system. This was result of the increased e-commerce use during the period of social detachment.